Progesterone receptors – animal models and cell signalling in breast cancer: Implications for breast cancer of inclusion of progestins in hormone replacement therapies - Schairer, Catherine (BioMed Central, 2002)
Progestins are included in menopausal hormone replacement therapy to counteract the increased risk for endometrial cancer associated with estrogen replacement therapy. Studies of hormone replacement therapy and breast cancer risk and of changes in mammographic density according to different regimens of hormone replacement therapy suggest that, for the most part, estrogen–progestin replacement therapy has a more adverse effect on breast cancer risk than does estrogen replacement therapy. Many questions remain unresolved, however, including risk associated with different regimens of estrogen–progestin replacement therapy, and whether the effects vary according to tumor characteristics, such as histology, extent of disease, and hormone receptor status.